Ngenger tradition and ideology transformation in inter-cultural communication - Anang Masduki; Dani Fadillah; Fajar Dwi Putra (Universitas Negeri Yogyakarta, 2021)
In Tempurejo, Ngawi, between the 1960s and 1970s, many Ponorogo residents chose to ngenger. Ngenger is living and working sincerely, not paying to a household of someone whose position is much higher in dignity, degree, and education. Children who come to ngenger the background are poor and have the ideology of the Nahdlatul Ulama (NU) mass organization or abangan. After finishing ngenger, the majority turned into Muhammadiyah activists and developed Muhammadiyah in Ponorogo. From the above problems, this study intends to reveal, First, the process of planting Muhammadiyah ideology. Secondly, there is an ideological transformation. This research was conducted in Ngawi and Ponorogo with qualitative descriptive methods. In-depth interviews, observation, and documentation of extracted data. The study results are the regeneration process carried out first; they see Muhammadiyah as an open, modern, professional organization. Second, families are open-minded and not doctrine. Third, the exemplary of educators and community leaders who have sincerity, the spirit of struggle, and the principle of the emphasis on the importance of Islamic da'wah. The ideological transition from originally an abangan Islam and NU to Muhammadiyah was because as long as the ngenger were introduced to Muhammadiyah organizations that were tolerant, open, modern, professional, and egalitarian.